EFEKTIVITAS PIJAT PERINEUM TERHADAP RUPTUR PERSALINAN DI PMB NELIS ANGGRAENI KLARI-KARAWANG - Nelis Anggraeni; Wiwit Desi Intarti; Lenny Irmawati Sirait (Jurnal Bina Cipta Husada, 2023)
Perineal rupture is a condition that occurs quite often in the normal delivery process. Perineal rupture is experienced by 85% of women during childbirth, according to the Ministry of Health of the Republic of Indonesia data on perineal rupture in Indonesia occurs in 75% of women giving birth vaginally in 2017. Perineal massage is a technique of massaging the perineum during pregnancy, or a few weeks before giving birth to improve elasticity or flexibility of the perineum so that blood flow in this area is smoother so that it does not hurt when stretching during labor so that it will prevent the occurrence of perineal tears and episiotomy. The aim of this study was to determine the effectiveness of perineal massage on the incidence of perineal rupture in women giving birth at BPM Nelis Anggraeni Klari - Karawang. The research method used in this study was a quasi-experimental design with a population of 30 people. Sampling was carried out using the total sampling technique where sampling will be carried out at BPM Nelis Anggraeni Klari-Karawang from March to April 2023. The data used is primary data. The research instrument uses checklist sheets and observation sheets. The research results based on the results of statistical tests using the T-Test test obtained a value of ρ = 0.025 (ρ <0.05). Conclusion: there is the effectiveness of perineal massage on perineal rupture in third trimester mothers at BPM Nelis Anggraeni Klari-Karawang. Suggestions for patients are expected to understand the benefits of perineal massage and be able to apply it during pregnancy, for health workers to provide information or knowledge about proper perineal massage as a non-drug therapy to reduce the incidence of perineal rupture during labour. Keywords: Effectiveness, perineal massage, perineal rupture, delivery